1999
DOI: 10.1128/jb.181.4.1292-1300.1999
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Purification and Properties of Betaine Aldehyde Dehydrogenase fromPseudomonas aeruginosa

Abstract: Betaine aldehyde dehydrogenase (BADH) (EC 1.2.1.8 ) catalyzes the last, irreversible step in the synthesis of the osmoprotectant glycine betaine from choline. In Pseudomonas aeruginosa this reaction is also an obligatory step in the assimilation of carbon and nitrogen when bacteria are growing in choline or choline precursors. We present here a method for the rapid purification to homogeneity of this enzyme by the use of ion-exchange and affinity chromatographies on 2′,5′-ADP–Sepharose, which results in a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(22 citation statements)
references
References 57 publications
4
17
1
Order By: Relevance
“…6 shows binding sites for Na + , K + and Mg 2+ at the dimerization interface of the protein and in the vicinity of the NAD-binding site. Binding of cations at similar sites have been reported previously (Muñ oz-Clares et al, 2010) and were shown to activate BADH/ALDH through facilitation of NAD(P) + association and to affect the tertiary and quaternary structures of the enzymes (Falkenberg & Strøm, 1990;Valenzuela-Soto & Muñ oz-Clares, 1994;Muñ oz-Clares et al, 2010;Velasco-García et al, 1999;Valenzuela-Soto et al, 2003;Gonzá lez-Segura et al, 2013;Garza-Ramos et al, 2013). Mg 2+ (Fig.…”
Section: Substrate-binding Site Of Sabadh and G234s-sabadhsupporting
confidence: 74%
See 1 more Smart Citation
“…6 shows binding sites for Na + , K + and Mg 2+ at the dimerization interface of the protein and in the vicinity of the NAD-binding site. Binding of cations at similar sites have been reported previously (Muñ oz-Clares et al, 2010) and were shown to activate BADH/ALDH through facilitation of NAD(P) + association and to affect the tertiary and quaternary structures of the enzymes (Falkenberg & Strøm, 1990;Valenzuela-Soto & Muñ oz-Clares, 1994;Muñ oz-Clares et al, 2010;Velasco-García et al, 1999;Valenzuela-Soto et al, 2003;Gonzá lez-Segura et al, 2013;Garza-Ramos et al, 2013). Mg 2+ (Fig.…”
Section: Substrate-binding Site Of Sabadh and G234s-sabadhsupporting
confidence: 74%
“…SaBADH was strongly inhibited by BA at concentrations of higher than 0.15 mM (Fig. 1d, Table 3), similarly to other BADHs (Velasco-García et al, 1999Falkenberg & Strøm, 1990;Valenzuela-Soto & Muñ oz-Clares, 1994;Boch et al, 1997). Detailed kinetic and inhibition studies of SaBADH have been published elsewhere (Chen et al, 2014).…”
Section: Enzymatic Activity Of Sabadhsupporting
confidence: 53%
“…Induction was noticed for the periplasmic components of ATP-binding proteins of ABC-type transporters involved in the transport of sugar (35B11), spermine/putrescine (7F12) and proline/glycine-betaine (83G4 and 1H11) ( Table 1 ). In general, Gram-negative bacteria achieve high intracellular concentrations of proline and glycine-betaine during osmotic or metal stress through increased transport ( Csonka, 1989 ; Velasco-Garcia et al ., 1999 ; Caldas et al ., 1999 ; Sharma and Dietz, 2006 ). Our results, underlying common pathways between heavy metal and osmotic stresses, are in accordance with a recent study on E. coli 's response to Cd toxicity ( Wang and Crowley, 2005 ).…”
Section: Resultsmentioning
confidence: 99%
“…Each determination was performed at least twice. One unit of activity is defined as the amount of enzyme that catalyses the formation of 1 μ mol of NADH per minute in standard assay (Velasco‐Garcia et al. 1999).…”
Section: Methodsmentioning
confidence: 99%